Implementasi Kebijakan Cukai Hasil Tembakau dalam Optimalisasi Penerimaan Negara: Analisis Van Meter dan Van Horn - Apriliasaidah, Dela; Fahrudin, Fahrudin (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the implementation of the tobacco excise policy at KPPBC TMP C Probolinggo and its contributing factors based on the Van Meter and Van Horn model. Using a qualitative case study approach, primary data were gathered through semi-structured interviews and field observations, while secondary data were collected from policy and performance documents. Data were analyzed using the Miles and Huberman interactive model and validated via source and technique triangulation. The results show that policy implementation runs effectively in supporting state revenue optimization through service, supervision, coaching, and enforcement activities. This effectiveness is driven by clear policy goals, Monitoring Center (MCR) technology, strong inter-agency coordination, supportive organizational structures, official commitment, and adaptive strategies toward local socio-economic conditions. Overall, the policy operates successfully through an adaptive implementation approach that balances fiscal enforcement with local economic sustainability.